(3fSeI GdSeQ HPcQ ef JTjY hTYQs - (3jhSa Hf jMji Hf GdMSjf GHf GdeDjO HGddg eMeO GHf GdbGSe GdUfYGfj,J (B1121 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CTYQ TjYI GdMb HGdCOH s
(3BNQgG (B:s
(3jfJgi HJQLeI CHj HMQ GdVMGc GdTgjQ HGdCVa Hf bjS GdeTghQ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B343s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B278 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs